2001 Turfgrass Research - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
With a summer noted for extended periods of temperatures over 100 °F, 2000 put turfgrass in our state through quite a test. As we enter the 2001 growing season, it's clear that some warmseason grasses were adversely affected by a cold winter. There is no rest for the weary attempting to growing quality turf in Kansas. This publication contains results of projects done throughout 2000 by K-State turfgrass researchers. You can see many of these projects in progress on August 2, 2001, at the Kansas Turfgrass Field Day at the John C. Pair Horticultural Research Center, Wichita. What questions can we answer for you? Maybe you’re curious about the best performing tall fescue cultivars for lawns, bermudagrasses for fairways, or bentgrasses for greens. Maybe you need to determine which tall fescue or fine fescue cultivars are best adapted to our state. As a superintendent, maybe you’d like to know how to convert a ryegrass fairway to something else. Some suggestions lie inside. Keep this research report handy - it can be useful all year long.
Keywords: Turfgrass; Disease control; Tall Fescue; Fine Leaf Fescue; Ryegrass; Bentgrass; Zoysiagrass; Buffalograss; Bermudagrass